Literature Review on LNG Supply Chain Risk Mapping - Muhammad Rakha Wirayuda; Imam Baihaqi; Mushonnifun Faiz Sugihartanto (International Journal of Business and Management Technology in Society, 2023)
Purpose – This study aims to identify and map potential risks in the Liquefied Natural Gas (LNG) supply chain, particularly in the context of global energy transition goals set by the 2015 Paris Agreement. With increasing reliance on LNG as a primary energy source to replace coal, understanding risks that may disrupt its supply is critical for power generation systems.Methodology – A Systematic Literature Review (SLR) was conducted by collecting and screening relevant journal articles from the Scopus database. The risk identification and classification were based on the SCOR (Supply Chain Operations Reference) model, which categorizes supply chain processes into Plan, Source, Make, and Deliver. The PRISMA protocol was applied to ensure transparency and rigor in document selection and content synthesis.Findings – A total of 21 risk factors were identified and mapped across the SCOR model. The highest concentration of risks (11 out of 21) occurs in the "Deliver" process, including supply disruptions, delivery delays, demand uncertainties, and overreliance on LNG as a primary energy source. These interconnected risks can trigger ripple effects such as increased electricity production costs and even the collapse of power grids due to imbalances in supply and demand.Originality – This study contributes to the literature by systematically integrating risk factors in the LNG supply chain with the SCOR framework and highlighting the vulnerabilities in the delivery stage. It offers practical insights for stakeholders in the LNG and power sectors to develop mitigation strategies, particularly in anticipation of future energy crises linked to LNG shortages.